Methods for comparing the performance of energy-conversion systems for use in solar fuels and solar electricity generation. Issue 10 (25th September 2015) - Coridan, Robert H.; Nielander, Adam C.; Francis, Sonja A.; McDowell, Matthew T.; Dix, Victoria; Chatman, Shawn M.; Lewis, Nathan S.
Abstract : We outline the significance and advantages of different metrics used to characterize photoelectrodes for electrochemical solar energy conversion. Abstract : The energy-conversion efficiency is a key metric that facilitates comparison of the performance of various approaches to solar energy conversion. However, a suite of disparate methodologies has been proposed and used historically to evaluate the efficiency of systems that produce fuels, either directly or indirectly, with sunlight and/or electrical power as the system inputs. A general expression for the system efficiency is given as the ratio of the total output power (electrical plus chemical) divided by the total input power (electrical plus solar). The solar-to-hydrogen (STH) efficiency follows from this globally applicable system efficiency but only is applicable in the special case for systems in which the only input power is sunlight and the only output power is in the form of hydrogen fuel derived from solar-driven water splitting. Herein, system-level efficiencies, beyond the STH efficiency, as well as component-level figures of merit are defined and discussed to describe the relative energy-conversion performance of key photoactive components of complete systems. These figures of merit facilitate the comparison of electrode materials and interfaces without conflating their fundamental properties with the engineering of the cell setup. The resulting information about the components can then be used in conjunction with a graphical circuit analysis formalism to obtain "optimal" system efficiencies that can be compared between various approaches. The approach provides a consistent method for comparison of the performance at the system and component levels of various technologies that produce fuels and/or electricity from sunlight.